Environmental implications of using 'underutilised agricultural land' for future bioenergy crop production. (October 2015) - Miyake, Saori; Smith, Carl; Peterson, Ann; McAlpine, Clive; Renouf, Marguerite; Waters, David
Abstract: Land use change effects have emerged as an important area of global bioenergy sustainability policy and research. 'Underutilised agricultural land' has been previously proposed as a potential option for future bioenergy feedstock production that may minimise the environmental and social challenges of land use change. However, this has not been well tested to date. Our research aims to evaluate whether conversion of these lands to selected bioenergy crops can lead to favourable environmental outcomes for eight indicators related to water quantity and quality, and terrestrial biodiversity. A spatially explicit evaluation framework based on GIS was developed to quantify the environmental effects of land use change. The land use change scenarios, established in a case study region in subtropical Queensland, Australia, were for the production of Pongamia and two native eucalypt species (Spotted gum and Chinchilla white gum) on (i) existing 'underutilised' open grazing areas, (ii) existing 'underutilised' forested grazing areas, and (iii) all available 'underutilised agricultural land' in the case study catchment, under both low and high management intensity. We found that environmental benefits can be gained in scenarios where (i) open grazing areas (e.g., pastures) were used; (ii) native woody perennial bioenergy crops were planted; and (iii) the new plantations were under low management intensity. Other scenarios resulted in reduced environmental outcomes. The results flagged the importance of careful planning and management strategies, and the need for future bioenergy policy to provide more detailed prescriptions concerning land use planning and management if 'underutilised agricultural lands' are used for future bioenergy crop production. Highlights: 'Underutilised agricultural land' can offer both positive and negative environmental outcomes. Bioenergy crop production on 'underutilised' open grazing areas is potentially beneficial. Successful outcomes require careful planning and management strategies. Bioenergy policy should provide detailed prescriptions for the use of these lands.